Revision of the genus Neoceruraphis Shaposhnikov, 1956 (Hemiptera: Aphididae) - Stekolshchikov, Andrey V. (Zootaxa, 2022)
The genus Neoceruraphis Shaposhnikov, 1956 with two species, is restored as a separate genus and not a synonym of Ceruraphis. This genus is fully revised, with descriptions or redescriptions of all known morphs of each species. Geographical points of species registrations are listed. All known and new data on the biology and life cycles of the species of genus are specified and analyzed. The genus Viburnaphis Pashtshenko, 1988 is considered a synonym of Neoceruraphis Shaposhnikov, 1956. Sappaphis viburnicola Sorin, 1983 becomes a secondary homonym of Neoceruraphis viburnicola (Gillette, 1909), so it must be replaced by the next oldest available name from among its synonyms—Viburnaphis pseudosensoriata Pashtshenko, 1988, which now becomes Neoceruraphis pseudosensoriata (Pashtshenko, 1988) comb. n. A possible way of the formation of the genus and the speciation that took place in it is discussed.